Perception and attitude of tobacco users towards tobacco in rural health institution. - Pathak, Pitambar (2013)
ABSTRACT: The present study aimed to investigate the current Perception and Attitudes of Tobacco users Towards Tobacco in Rural Health Institution. The study was conducted among the different ethnic, who are visited as a patient in Pipara Rural Hospital above 15 years living in Kapilvastu district Banganga VDC Ward no. One to Nine. The information was collected through OPD. The respondents were patient visit in Pipara Hospital. The number of respondents was 120 tobacco users. This study was based on primary source of data. Primary data were collected through an interview with the patients visiting in Pipara Rural Hospital of Kapilvastu District. The study was conducted from Pipara Rural Hospital, OPD patients above 15 years, who were tobacco/smoke addict. The study was conducted for to find out the socioeconomic and demographic status, perception and attitude (by Likert analysis method) of tobacco user/patients from Banganga V.D.C. Quantitative research using primary data. Respondents of tobacco user and smokers were 100 percent, among them 75 percent were male user and 25 percent were female user. Among them 68 percent tobacco users were patients involved in agriculture. Majority were i.e.57 percent (Magar/Tharu/Newar) Janajati users, lower user were Dalit (Sarki, Kami) 8 percent, and medium people were Brahun/Chhetri 35 percent. Easy to consume 62 percent were surti users and 38 percent were churot/cigarette users. 98 percent knows the bad effects of tobacco but consumed tobacco. About 51 percent started tobacco since the age within 15-19. More than one-fourth user 27 percent used tobacco 16 above time a day. Some user answer that they one fourth 24 percent take tobacco frequently, most of the tobacco user answer that they spent more than Rs.20 per day for tobacco products. More than 28 percent feel that they have recent effects of tobacco minor health problem. About 24 percent patients are aware of taking tobacco to cancer disease. More than 75 percent tobacco users has strong knowledge on smoking and using tobacco by examining Likert analysis but they practice smoking tobacco which ruins and a effects on their health. On the basis of this finding there should be conduction of awareness program, inform the people by local agencies and all the researches had to be used successful effective program. There are various causes of tobacco consuming. Likewise that needs to focus on the macro and micro causes of it and independent variables. Perception, attitude, practice of tobacco use and smoking is high then prevalence, consumption and effects on health are greater. So, integrated awareness camp, behaviour change, communication should be action by government, all sector such as; teacher, community member, leader, doctor, different youth club, mother committee, health volunteer and all the related agencies. So it is not easy by single effort by researcher only.